Suitability of walnut and pistachio shells as soilless substrates for producing Genovese basil in aquaponic systems - Suárez-Cáceres, Gina P.; Lokuhitige, Sandamali; Kaufman, Nathan T.; Alghaithy, Alharith; Hishaw, Mikaila B.; Donis-Gonzalez, Irwin R.; Fernández-Cabanás, Víctor M.; Gross, Jackson A. (Frontiers in Horticulture, 2025)
IntroductionThe use of agricultural by-products, such as walnut and pistachio shells, is emerging as a sustainable substrate alternative to conventional substrates in soilless farming systems like hydroponics and aquaponics. These materials offer a promising solution for agri-waste management while advancing circular economy objectives in sustainable agriculture.MethodsThe present study evaluates the performance of crushed walnut shell (CWS) and line-waste pistachio shell (LWPS) as partial to complete replacements for coconut coir (CC) in decoupled aquaponic systems, using Genovese basil (Ocimum basilicum) as a model crop. Two independent experiments were conducted concurrently, one for each nutshell substrate (n=6 replicate trays). Each experiment included nine treatments: a control group (50% peat moss/50% perlite), four nutshell-based blends (10%, 25%, 33%, and 50% of either CWS or LWPS), and four CC-based blends at the same inclusion rates. Plant growth metrics, including height, number of nodes and leaves, SPAD chlorophyll index, fresh and dry shoot weight, and root development were measured to assess treatment performance.ResultsOverall, basil grown in lower inclusion rates of CWS and LWPS media performed comparably to those grown in CC-based media. However, growth suppression was observed in the 33% and 50% CWS treatments, likely due to juglone toxicity. In contrast, LWPS exhibited a modest growth benefit at 25%, before declining at higher levels, which may be acributed to reduced water holding capacity.DiscussionThese findings suggest that walnut and pistachio shells can serve as effective components of soilless growing media when used at moderate inclusion rates. While higher concentrations presented limitations, low to moderate inclusion levels yielded growth performance comparable to that of CC. These findings support the potential of regionally sourced nutshell by-products as viable alternatives to imported growing media, contributing to a more diversified and resilient horticultural supply chain.